Quality of work life and Generation Y: How gender and organizational type moderate job satisfaction. Issue 1 (18th October 2019) - Muskat, Birgit; Reitsamer, Bernd F.
Abstract : Purpose: The purpose of this paper is to examine how quality of work life (QWL) influences job satisfaction and to test if gender and organizational type moderate this relationship for Generation Y (Gen-Y). Design/methodology/approach: Questionnaire data were collected from 328 Gen-Y employees in European hospitality businesses. Drawing on generational theory, social role theory and person–environment (P–E) fit theory, the authors discuss how gender and organizational types (i.e. independent vs corporate structures) moderate Gen-Y's QWL–job satisfaction relationship. Findings: The findings of the paper are as follows: first, gender and organizational type influence the QWL–job satisfaction relationship for Gen-Y. Second, job security does not change job satisfaction levels for female employees while high levels of job security negatively influence job satisfaction for male employees. Third, receiving appreciation at work increases job satisfaction for both women and men but, when receiving little appreciation at work, women remain more satisfied. Fourth, having opportunities to contribute to decisions positively affects Gen-Y's job satisfaction. Fifth, having the right to say is more important in independent organizations, while the opportunity to realize an employee's own potential leads to higher job satisfaction in corporate organizations. Originality/value: The study contributes to the limited empirical scholarly research, adding to a deeper understanding of influencing factors of Gen-Y's QWL–job satisfaction relationship.